Targeting asymptomatic malaria: assessment of community-based active case detection in the Peruvian Amazon - Moreno-Gutierrez, Diamantina (2019)
Background: Faced with the resurgence of malaria in the Peruvian Amazon since 2012, malaria surveillance was enhanced by adding a local active case detection (ACD) strategy to the routine passive case detection (PCD) as a reactive measure in selected communities with unusual number of cases during high transmission season (HTS). We assessed the short-effectiveness of this local ACD-based strategy in four Peruvian Amazonian riverine communities. Methods: A cohort study was conducted in June-July 2015 in Mazan, Loreto. Four consecutive ACD interventions (using light microscopy (LM) and treatment of confirmed infections) at intervals of 10 days were conducted in four riverine communities (Gamitanacocha-GAM, Primero de Enero-PRI, Libertad-LIB, and Urco Miraño-URC) that previously reported unusual number of cases. Blood samples were also collected on filter paper for later PCR. The effectiveness of the local strategy was calculated by dividing the number of infections detected in ACD visits using LM by the total number infections identified by PCR. Results: Of the total 933 censused people in the area, 88.1% were found in at least one of the four ACD visits. 54.2% had confirmed infections by PCR; among them 5 had two infections during the study period. Most infections were asymptomatic (270/451, 59.9%) and due to P. vivax (360/451, 79.8%). P. falciparum infections and P. vivax-P. falciparum co-infections accounted for 15.3% and 4.9% of total infections. Only 22.8% of the total 451 PCR confirmed infections were accurately detected using LM during the four ACD visits. Children aged 5-14 years, and farming as main economic activity were associated with P. vivax infections. Conclusion: Although repeated and consecutive ACD interventions using LM increase the opportunity of detecting and treating malaria infections during HTS, the number of detected infections would be far from the “true” number of infections detected by a highly sensitive diagnostic test.